2015
DOI: 10.1007/s11605-014-2610-5
|View full text |Cite
|
Sign up to set email alerts
|

Peroral Endoscopic Myotomy (POEM) for Esophageal Primary Motility Disorders: Analysis of 100 Consecutive Patients

Abstract: This study represents the largest POEM series to date that includes objective data. Despite reflux in one/three of patients, POEM provides excellent relief of dysphagia (97%) and chest pain (91.5%) for patients with esophageal spastic disorders with acceptable procedural morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(105 citation statements)
references
References 26 publications
7
92
0
6
Order By: Relevance
“…19,36,[38][39][40][41][42] Most of these series demonstrated a sustained clinical success of POEM in > 90% of patients, with the follow-up duration ranging from 12 months to > 36 months. 19,36,[38][39][40][41][42] However, one international prospective multicenter study showed some decline in clinical success over time. 39 Von Renteln et al 39 demonstrated a 97% treatment success at 3 months, 88.5% at 6 months, and 82.4% at 12 months, which significantly declined from the initial treatment success.…”
Section: Long-term Outcomesmentioning
confidence: 98%
“…19,36,[38][39][40][41][42] Most of these series demonstrated a sustained clinical success of POEM in > 90% of patients, with the follow-up duration ranging from 12 months to > 36 months. 19,36,[38][39][40][41][42] However, one international prospective multicenter study showed some decline in clinical success over time. 39 Von Renteln et al 39 demonstrated a 97% treatment success at 3 months, 88.5% at 6 months, and 82.4% at 12 months, which significantly declined from the initial treatment success.…”
Section: Long-term Outcomesmentioning
confidence: 98%
“…It has shown that more than 90% of patients with type III achalasia were successfully cured by POEM with appropriate length of myotomy. Since POEM was first performed in Japan for resolving uncomplicated achalasia, its excellent outcomes allowed us to expand the range of disorders to include advanced sigmoid achalasia, failed surgical myotomy and even other spastic esophageal motility disorders [14] such as distal esophageal spasm [15] and Jackhammer esophagus [16]. The outcome of POEM for achalasia remains excellent up to 3 years after operation [12].…”
Section: Treatment Strategies For Achalasia Based On Subtypesmentioning
confidence: 99%
“…Symptom relief in achalasia patients following POEM is excellent, as dysphagia and chest pain were resolved at rates of 98 % and 92 % respectively in the largest retrospective series to date [ 4 ]. In nonachalasia patients (DES, nutcracker esophagus, hypertensive LES) symptom relief was less impressive but sill greater than 70 % [ 4 ].…”
Section: Discussionmentioning
confidence: 98%